2021
DOI: 10.21203/rs.3.rs-587669/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Autism and Chronic Ill Health: An Observational Study of Symptoms and Diagnoses of Central Sensitivity Syndromes in Autistic Adults

Abstract: Background Autistic adults, particularly women, are more likely to experience chronic ill health than the general population. Central sensitivity syndromes (CSS) are a group of related conditions that are thought to include an underlying sensitisation of the central nervous system; heightened sensory sensitivity is a common feature. Anecdotal evidence suggests autistic adults may be more prone to developing a CSS. This study aimed to investigate the occurrence of CSS diagnoses and symptoms in autistic adults,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 41 publications
2
14
3
Order By: Relevance
“…Additionally, the positive relationship between autistic traits and somatic symptom burden remained after controlling for age, sex, and generalized anxiety, in contrast to prior findings in an adult autistic sample 10 . However, it is notable that the prior study also controlled for self-reported Table 3.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Additionally, the positive relationship between autistic traits and somatic symptom burden remained after controlling for age, sex, and generalized anxiety, in contrast to prior findings in an adult autistic sample 10 . However, it is notable that the prior study also controlled for self-reported Table 3.…”
Section: Discussioncontrasting
confidence: 99%
“…As a measure of total somatic symptom burden across the remaining symptoms, we took the mean score of all nonmissing items (i.e., up to 14 items for females and 13 for males), multiplied that score by 15, and rounded to the nearest integer value in order to approximate the 0-30 distribution of the original PHQ-15 questionnaire. Total scores on this measure can be qualitatively interpreted as minimal (0-4), mild (5-9), moderate (10)(11)(12)(13)(14), and severe (≥15) 15 .…”
Section: Somatic Symptom Burden Was Measured With a Modified Version Of The Patient Healthmentioning
confidence: 99%
See 3 more Smart Citations